2018
DOI: 10.6000/1927-5129.2018.14.33
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Activities of Carica papaya Linn

Abstract: Carica papaya is a tropical fruit, present in orange red to yellow orange color. The whole plant including fruit, leaves, roots, peel, bark, seed and pulp served as medicine. It is rich in minerals, carotenoids, vitamins, alkaloids, enzymes, lycopene, and flavonoids that provide the papaya with special importance. It is used as a remedy for the treatment of many skin infections, anti fungal, anti viral infections. Its milky juice extracted and dried is used as medicine for digestive disorders and as toothpaste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The root cause is linked to phytochemicals such as alkaloids, flavonoids, saponins, glycosides and phenolic compounds, having a chemical activity similar to reproductive hormones; hence mimicking hormone-like functions ( Verma et al, 2016 ; Soni et al, 2016 ) . Studies on alkaloids, flavonoids, saponins, and phenolic isolates reported they disrupt the oestrus patterns in animals ( Ifeanyi et al, 2011 ; Verma et al ., 2016 ; Soni et al ., 2016 ; Fatima & Shahid, 2018 ) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The root cause is linked to phytochemicals such as alkaloids, flavonoids, saponins, glycosides and phenolic compounds, having a chemical activity similar to reproductive hormones; hence mimicking hormone-like functions ( Verma et al, 2016 ; Soni et al, 2016 ) . Studies on alkaloids, flavonoids, saponins, and phenolic isolates reported they disrupt the oestrus patterns in animals ( Ifeanyi et al, 2011 ; Verma et al ., 2016 ; Soni et al ., 2016 ; Fatima & Shahid, 2018 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Carica papaya black seeds are edible, having sharp and spicy taste; hence, its ground form is used as an alternative for black pepper ( Sindhu et al ., 2019 ) . Studies have reported that these seeds have more potent medicinal properties as compared to other parts of the papaya plant due to their strong antioxidant properties ( Zhou et al, 2011 ; Fatima & Shahid, 2018 ; Otsuki et al, 2010 ; Sindhu et al ., 2019 ) ; for example we have antibacterial ( E.coli , Salmonella and Staphylococcus infections), liver protection, anthelminthic, typhoid treatments ( Sindhu et al ., 2019 ), nephroprotective effects ( Otsuki et al ., 2010 ) and in folk medicine it is an intestinal worm expellant in humans and ruminants.…”
Section: Introductionmentioning
confidence: 99%
“…The second advantage of papaya root is that it can be used as a medication to help cure rheumatism, a condition that is more common among elderly individuals. We also employ papaya blossoms, leaves, and roots in a variety of other situations (Urooj, et al;.…”
Section: Rootmentioning
confidence: 99%